ENVIRONMENTAL HEALTH RISK ASSESSMENT OF TOTAL SUSPENDED PARTICULATE EXPOSURE TO EMPLOYEE OF PT SEMEN PADANG (Proceedings of the International Conference on Public Health, 2017)
The cement industry has negatively impacts in air pollution that affect to the respiratory system. The aims of this study was to determine the level of environmental health risks through the risk analysis of Total Suspended Particulate (TSP) exposure to employee of PT Semen Padang, West Sumatra, Indonesia. This study uses environmental health risk analysis (EHRA) method that aims to calculate the level of risk received by a population due to environmental exposure. Research was conducted on December 28, 2015 until June 27, 2016. The number of sample were 32 respondents. The sampling technique used was accidental sampling. TSP concentration measurements by using the tool Staplex Model TFIA series High Volume Air Samplers (HVAS). The results based on the value of the intake lifetime exposure to TSP inhaled indicate that the area Coal mill and Cement mill on the employees in the Production Department II / III PT Semen Padang at risk of developing respiratory problems to the value of RQ > 1 and based on the value of the intake realtime exposure TSP inhaled were not at risk respiratory disorders with RQ
Keywords: total suspended particulate, exposure, environmental health risk assessment